Cream Puff Gebu's / Norazreen Mat Raius - MAT RAIUS, NORAZREEN (2019)
Cream puff is one of the popular dessert nowadays in Klang Valley. I decided to choose and sell the cream puff for my social media business because it has high demand from customers, also will earn more profit. I put the name of my business is Cream Puff Gebu's (CPG) which is focused on the food production in Malaysia. Besides, the shape and custard filing make this creampuff looks tempting and delicious. Moreover, it is suitable to serve for any occasion. To make the cream puff, is not that difficult and the ingredients are easy to find at local shop or supermarket.